EFFECT OF COOPERATIVE TYPE STAD AIDED BY MACROMEDIA FLASH TOWARD STUDENTS’ LEARNING OUTCOMES - Gita Ravhani Anugrah; Makmur Sirait (UNIVERSITAS NEGERI MEDAN, 2014)
Abstract The purpose of this research was to see the effect of Cooperative Learning Model Type STAD Aided by Macromedia Flash Media toward Students’ Learning Outcomes in cognitive, affective, and psychomotor domain. The research method was quasi experimental. Using a pre-test-post-test comparison-group design and t test for independent samples, it was found that after approximately 3weeks students (n = 25) who were instructed using cooperative STAD aided by macromedia flash significantly higher scores on post-test than did students (n = 25) who were instructed using Direct Instruction model.Testing of hypothesis for postest showed that tcount > ttable. Using observation method in affective and psychomotor domain, it was found that average mark of affective and psychomotor students in experiment class was higher than control class. The study conclude that there was the significant effect of Cooperative Learning Model Type STAD Aided by Macromedia Flash Media toward Students’ Learning Outcomes. Keywords: Cooperative learning, STAD, Macromedia Flash, Learning Outcomes